THE INFLUENCE OF FINANCIAL PERFORMANCE ON STOCK PRICES IN THE PROPERTY SECTOR AVAILABLE ON THE INDONESIAN STOCK EXCHANGE - Dela Angreni; Muchriana Muchran; Muhammad Khaedar Sahib (CV. AFDIFAL MAJU BERKAH, 2024)
The aim of this research is to determine the effect of financial performance on share prices in the property sector listed on the IDX. The population in this research is property sector companies listed on the Indonesia Stock Exchange (BEI), with a sample of 12 companies. This research was conducted using quantitative methods with the variables used in this research being Financial Ratios which are proxied by Current Ratio (CR), Return On Assets (ROA), Price Earning Ratio (PER), and Debt Equity Ratio (DER). The data analysis techniques used in this research are the classical assumption test, multiple linear regression analysis, hypothesis testing with partial tests (t tests) and determination tests with the help of SPSS software. The results of this research show that the Current Ratio (CR) has a positive and significant effect on the share prices of property companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. Which means that the level of a company's ability to fulfill all its short-term obligations has a positive and significant effect on share prices, Return On Assets (ROA) has a positive and significant effect on the share prices of listed property companies (BEI) for the 2018-2022 period. Which means that the return on assets of a company has a positive and significant effect on share prices, the Price Earning Ratio (PER) has a positive and significant effect on the share prices of property companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. Which means PER has increased in share prices. And the Debt Equity Ratio (DER) has no effect on the share prices of property companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. Which means that the level of a company's ability to use owner's capital has no effect on share prices.